2011
DOI: 10.1111/j.1365-2184.2011.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Two novel aspirin analogues show selective cytotoxicity in primary chronic lymphocytic leukaemia cells that is associated with dual inhibition of Rel A and COX-2

Abstract: Our results demonstrate therapeutic potential of 4HBZ and are consistent with a mechanism involving suppression of Rel A nuclear translocation and inhibition of COX-2 transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Another study showed that the deficiency of sharp in leads to TNF-dependent inflammation of various organs in mice while its deletion resulted in a significant reduction in the E3 ligase linear ubiquitin chain assembly complex (LUBAC) which subsequently attenuated TNF-a and CD40-mediated activation, suggesting the role of LUBAC in NF-KB activation (39). The pro-survival factor CD40 ligand (CD40L) can induce COX-2 mRNA expression essential for the synthesis of the prostaglandins (10). Thus, using anti-inflammatory drugs and/or anti-oxidants can essentially contribute to the management of inflammation homeostasis.…”
Section: Cyclooxygenase-2 Expression Proliferation and Cancer Vs Simmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that the deficiency of sharp in leads to TNF-dependent inflammation of various organs in mice while its deletion resulted in a significant reduction in the E3 ligase linear ubiquitin chain assembly complex (LUBAC) which subsequently attenuated TNF-a and CD40-mediated activation, suggesting the role of LUBAC in NF-KB activation (39). The pro-survival factor CD40 ligand (CD40L) can induce COX-2 mRNA expression essential for the synthesis of the prostaglandins (10). Thus, using anti-inflammatory drugs and/or anti-oxidants can essentially contribute to the management of inflammation homeostasis.…”
Section: Cyclooxygenase-2 Expression Proliferation and Cancer Vs Simmentioning
confidence: 99%
“…Willow bark extract, mainly contains p-D-salicin [1], and other SP complexes have been shown to down regulate cell proliferation, inhibit cell cycle, and subsequently induce apoptosis in different cell lines (8)(9)19). Other studies have shown that 2-HBA [2] or its metal ion complexes, including Na [8], Li [9], Ca [10] or Zn [11 and 12] (Fig. 4), can modulate these cellular processes and subsequently inhibit growth mostly at concentrations in the millimolar range (8)(9).…”
Section: Cell Proliferation Vs Apoptosis and Simple Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 ferent cancer cells [4][5][6][7] . The assessed compounds include hydroxybenzoate (HB), 2-acetylbenzoic acid (2-ABA) or aspirin, and its precursor 2-hydroxybenzoic acid (2-HBA).…”
mentioning
confidence: 99%
“…The mechanism of these compounds is to induce apoptosis via the intrinsic pathway involving the upregulation of the expression of p53, Bax and caspase-9 [4,10,12] . In parallel, these compounds downregulated Bcl-2, an antiapoptotic protein that is able to suppress cytochrome c release and subsequently caspase-3.…”
mentioning
confidence: 99%